AMS 14C dating and wood identification in ancient timber structures in Shanxi Province, China. (June 2017) - Dong, Meng-Yu; Lu, Yun; Jiang, Xiao-Mei; Wang, Wei-Bin; Zhou, Yu-Cheng; Zhao, Guang-Jie; Zhou, Hai-Bin; Yin, Ya-Fang
Abstract: Shanxi Province in the north west of China is one of the centres of ancient Chinese civilization. Archaeological records from this region are a valuable legacy of ancient culture in China. Many historical buildings have been preserved up to the present time. Forty-one archaeological wood samples were taken from twelve timber structures that are in the northern, central, southern and south-eastern regions of Shanxi Province, China. The AMS 14 C dates were calibrated and compared to the dates in the historical records to establish accurate calendar dating of the timbers using radiocarbon analyses, when it came to the construction of the buildings and the times when maintenance work was carried out on them. The reusing of certain timbers was investigated. All the samples were identified using a microscope; they were identified as eleven timber-tree genera. The most common species used for the ancient buildings concerned was Ulmus, followed by Larix, Populus and Quercus . While guaranteeing quality and utility, these taxa were mostly used in the columns, flower arms, cap blocks, bracket sets etc. The principle and trend of the wood selection involved were pointedly restricted by means of transportation, because the ancient timbers used in the buildings were mostly gathered from the local wild wood resources in the areas nearby. Highlights: Establishing calendar dating by AMS 14 C dates with historical records of timber. Common timber-tree genera used for ancient buildings are confirmed microscopically. The principle of wood selection from surrounding qualified resources is proposed.